SISTEM RECOMMENDER PROGRAM STUDI FMIPA MENGGUNAKAN METODE PREFERENCE RANGKIN ORGANIZATION FOR ENRICHMENT EVALUATION (PROMETHEE) - Marlinda, Linda; S.W., Sulistianto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The selection of study programs plays an important role in one’s success to determine his future. One of the risks associated with choosing a study is the incompatibility with current job vacancy needs of a company that significantly affects the student’s future. Because there are many criteria to be considered, then through this recommender system, students can find out what areas are most appropriate for them. The system is built on the PROMETHEE method. When a student fills out a questionnaire, he / she must be consistent with his / her answer to get the best output based on his / her will and characteristics. This study uses a descriptive analysis method presents a summary of survey results and interviews of prospective students who want to choose a study program, especially FMIPA in several universities in accordance with the codification connected with Job Career so that it can be a reference for prospective students in finding a job. Keywords: System Recommender, Study Program, Multikriteria, Promethee